Further intracellular proteins and signaling pathways regulated by angiotensin-(1-7) in human endothelial cells - Meinert, Christian; Wieland, Thomas; Walther, Thomas (Data in Brief, 2017)
In 2016, Meinert et al. (doi: 10.1016/j.jprot.2015.09.020) published the first 25 proteins in a protein array regulated in Human Umbilical Vein Endothelial Cells (HUVEC) by the heptapeptide angiotensin (Ang)-(1-7) and the first 10 intracellular signaling cascades at different time points. This supporting data article shows further proteins and pathways stimulated by Ang-(1-7) in human endothelial cells at time points of 1h, 3h, 6h, and 9h. HUVECs were stimulated with Ang-(1-7), and regulated proteins were identified via antibody microarray. Bioinformatics software IPA was used for association of regulated proteins to metabolic pathways.
Online 8 December 2016
Gesehen am 25.09.2018